Optimalisasi Peradilan Perdata dalam Menjawab Sengketa Bisnis Berbasis Teknologi Informasi - Zebua, Elbryan Alfandi Damai Sonifati; Purwati, Ani (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2026)
The development of information technology has fundamentally changed business transaction patterns through the use of electronic contracts, digital platforms, and online transaction systems. This transformation has not only increased the efficiency of business activities but also created new complexities in business dispute resolution, which civil courts must address. This research is motivated by the suboptimal performance of civil courts in handling IT-based business disputes, particularly regarding procedural law, electronic evidence, and institutional readiness. The purpose of this research is to analyze how civil courts can optimize their handling of IT-based business disputes. The method used is normative legal research with statutory, conceptual, case-based, comparative, and historical approaches. The results show that although national regulations have recognized the validity of electronic transactions and evidence, judicial practice still faces normative and technical obstacles. This research concludes that optimizing civil justice requires procedural law reform, increased judicial capacity, and the integration of information technology to ensure legal certainty, justice, and the effectiveness of digital business dispute resolution.